Rheumatoid arthritis and cardiovascular diseases: close relatives or friends? - A. V. Gordeev; Yu. A. Olyunin; E. A. Galushko; E. G. Zotkin; A. M. Lila (Современная ревматология)
The problem of comorbidity is widely discussed in modern medical literature. Its role in rheumatic diseases is of particular interest due to their multifactorial nature and the involvement of a wide range of pathogenetic mechanisms. For many years, researchers around the world have noted correlations between the presence of active autoimmune disorders and the complicated course of cardiovascular diseases. A deeper understanding of the pathogenetic mechanisms at the present stage of development of rheumatology allows us to take a fresh look at the relationship between atherosclerosis and rheumatoid arthritis. The definition of multimorbidity developed in recent years and the results of recent scientific studies may contribute to a more correct choice of tactics for managing patients with a combination of these two diseases.